(untitled) (Research, Society and Development, 2020)
To analyze the difficulties faced by nursing professionals in assisting burn patients; to verify the main complications during the burn treatment period and to identify problems in the nurse / patient and family interpersonal relationship. Methodology This is a descriptive, exploratory study with a qualitative approach, in which the sample consisted of nursing professionals, in a reference hospital in a city in the interior of the northeast. For the collection of empirical material, a semi-structured script was used, respecting the ethical aspects of Resolution 466/12 of the National Health Council. As for treatment, the speeches were submitted to content analysis of the thematic type, proposed by Bardin. Results The results of this study point to several difficulties faced by the nursing team, among which the constant need for a doctor in the sector, as the care for burned patients requires multidisciplinary treatment and nursing alone cannot offer a treatment that is capable of contemplating the complexity of the situation. The most evident complications in a burned patient is the risk of infection because it is a culture medium. Respondents showed difficulties when it came to interpersonal relationships between professionals, family and patient. Conclusion The results of this study point out several difficulties faced by the nursing team, among which, the constant need for a doctor in the sector, to be able to have comprehensive assistance. With regard to complications in burns, it was seen that the patient’s chance of developing infections is great, due to the fact that he has a great exposure and because the burn is a culture medium. Because it is a sector that requires a lot of care both in direct assistance to the patient, as well as how to deal with family members who are often upset, the nursing team needs to be psychologically prepared to know how to deal with burned patients.